2019
DOI: 10.1002/ece3.4957
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different cold‐temperature regimes on development, growth, and susceptibility to an abiotic and biotic stressor

Abstract: Global climate change is expected to both increase average temperatures as well as temperature variability. Increased average temperatures have led to earlier breeding in many spring‐breeding organisms. However, individuals breeding earlier will also face increased temperature fluctuations, including exposure to potentially harmful cold‐temperature regimes during early developmental stages. Using a model spring‐breeding amphibian, we investigated how embryonic exposure to different cold‐temperature regimes (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
1
5
0
1
Order By: Relevance
“…Indeed, only the eggs located at the pond surface may be impacted by cold air temperatures, which do not concern the entire population. In addition, pre-metamorphosis stages have variable sensitivity to cold temperature (Moore, 1942;Herreid and Kinney, 1967;Muir et al, 2014;Wersebe et al, 2019). Earlier breeding increased the risk of frost exposure at both elevations, but this may also allow juveniles to reach larger size at metamorphosis and thus increase survival probability as adults (Altwegg and Reyer, 2003;Loman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only the eggs located at the pond surface may be impacted by cold air temperatures, which do not concern the entire population. In addition, pre-metamorphosis stages have variable sensitivity to cold temperature (Moore, 1942;Herreid and Kinney, 1967;Muir et al, 2014;Wersebe et al, 2019). Earlier breeding increased the risk of frost exposure at both elevations, but this may also allow juveniles to reach larger size at metamorphosis and thus increase survival probability as adults (Altwegg and Reyer, 2003;Loman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We additionally found that wood frog tadpoles from the later-breeding cohort of 2018 were less tolerant of NaCl than tadpoles from the earlier-breeding cohort of the same year. While direct exposure to cold temperatures has been documented to lower immune responses [ 16 , 54 ], reduce larval growth and development [ 63 ], and interact synergistically with other stressors [ 57 ], it is important to note that in this study, tadpoles were not directly exposed to the cold temperatures of the parental environment. Thus, the reduced baseline tolerance to NaCl of the late breeding cohort may reflect cross-generational consequences of parental exposure to suboptimal temperatures [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The later-breeding R. sylvatica cohort in 2018 experienced a more severe winter weather event than the later-breeding cohort in 2019 (5 versus 2 days of freezing temperatures in 2018 and 2019, respectively). The later-breeding cohort in 2018 therefore likely experienced greater physiological stress from the freeze than the later-breeding cohort in 2019; there are costly physiological responses to low temperatures [ 19 , 63 ] and maternal stress is often transferred to developing eggs [ 18 , 62 ] in a variety of herpetofauna. The higher level of stress experienced by the later-breeding cohort in 2018 may be one potential cause of reduced offspring baseline tolerance to NaCl compared to that in 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing global temperature has a profound effect on the functioning of biological systems, e.g. it advances the timing of spring events (earlier arrival and breeding of migrant birds, earlier Communicated by W. Hughes appearance of butterflies, earlier spawning of amphibians or plant flowering), shifts species distribution poleward in latitude and upward in elevation, alters community composition and could result in the widespread phenological desynchronization among species (Walther et al 2002;Parmesan and Yohe 2003;Thackeray et al 2016;Wersebe et al 2019). The importance of temperature was neatly emphasised in this sentence: 'unlike many other variables that concern biologists, the temperature is not just a property of life; it is a property of matter.…”
Section: Introductionmentioning
confidence: 99%